2021
DOI: 10.4103/2452-2473.301913
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of patients with sternal fracture

Abstract: OBJECTIVES: Sternal fractures (SFs) are rare pathologies that mainly occur as a result of traffic accidents, which can cause mortality due to concomitant complications. In this study, we aimed to evaluate clinical processes and termination status of patients diagnosed with a SF in the emergency department. METHODOLOGY: Patients diagnosed with a SF in the emergency department during 8 years were retrospectively reviewed. The demographic and clinical characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…Concomitant injuries alongside rib fractures such as haemothorax and lung contusions were more evident in their analysis of SF patients. [ 14 ] This evidence is also supported by Yakar et al [ 15 ] who identified that MVA was the most common mechanism of injury in their SF patients (66.4%, N = 128) and the most common thoracic pathology accompanying SFs was rib fractures (36%, N = 128). Despite the evidence displaying the prevalence of rib fractures and its associated risk in the context of SF, there is very little evidence to review regarding bilateral rib injury.…”
Section: Discussionsupporting
confidence: 61%
“…Concomitant injuries alongside rib fractures such as haemothorax and lung contusions were more evident in their analysis of SF patients. [ 14 ] This evidence is also supported by Yakar et al [ 15 ] who identified that MVA was the most common mechanism of injury in their SF patients (66.4%, N = 128) and the most common thoracic pathology accompanying SFs was rib fractures (36%, N = 128). Despite the evidence displaying the prevalence of rib fractures and its associated risk in the context of SF, there is very little evidence to review regarding bilateral rib injury.…”
Section: Discussionsupporting
confidence: 61%
“…Les patients étaient pour la plupart de sexe masculin. L'âge moyen dans notre étude est en accord avec celui rapporté par plusieurs auteurs dans la littérature [5,8,9]. La symptomatologie est dominée par une douleur modérée à intense localisée au sternum, exacerbée par la toux ou les éternuements.…”
Section: Discussionunclassified
“…Le recours au scanner thoracique est nécessaire dans la plupart des cas pour la mise en évidence de la fracture du sternum et le bilan des lésions associées [11]. De nombreuses lésions associées peuvent accompagner les fractures de sternum avec des proportions qui diffèrent d'une étude à une autre [8,5,10]. Ces lésions peuvent aller de la simple fracture des côtes à une contusion pulmonaire voire un hémo-pneumothorax.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, Heidelberg, Uhlich [ 26 ] reported that displacement cannot predict fracture displacement and its severity. A recent study conducted by Yakar, Baykan [ 27 ] on 128 sternal fracture patients showed that car traffic accidents are the most common cause of these accidents. Localization of fracture was not associated with abnormal ECG findings in the study.…”
Section: Discussionmentioning
confidence: 99%